Poster: Is Hybrid Working Good for Health, Safety and Wellbeing? An Overview of Systematic Reviews - Gorjifard, Roya; Crawford, Joanne; Blumenfeld, Stephen; Peace, Christopher; Bowe, Stephen (New Zealand Journal of Health and Safety Practice, 2024)
Hybrid working: Working from home or away from an employer’s location, part-time or full-time, using information technology (IT). What do we know about the health and wellbeing of hybrid workers so far?